Accounting Information Systems Quality Through Information Technology and User Competence - Darma, Jufri; Nurwendari, Weny; Sriwedari, Tuti; Nurhayani, Ulfa (Universitas Pendidikan Indonesia, 2024)
This research examines the impact of information technology and user competence on the efficiency of accounting information systems. Using a survey approach, the study involves 47 regional government organizations. Hypothesis testing is conducted through structural equation modeling (SEM) with data analyzed using Smart PLS-SEM. The study found that user competence significantly enhances the quality of accounting information systems, while information technology has minimal impact. In the Medan City Government, this highlights the crucial role of user competence in ensuring system effectiveness, with technology playing a lesser role. The Medan City Government remains focused on enhancing the competence of its personnel in utilizing accounting information systems. Additionally, continuous efforts are made to adapt the existing information technology to meet the evolving needs of users. This study offers new insights into how information technology and user competence jointly influence the quality of accounting information systems in the Medan City Government.